AB0959 Ultrasonograhic Tendon Alteration in Relation to Parathyroid Dysfunction in Chronic Hemodialysis Patients. (9th June 2015) - El-Azizi, N.O.; Hussein, D.; Abdelmeged, A.; El-Hoseiny, S.; Hamada, A.; Sabry, M.
Abstract : Background: The etiology of tendon alteration in chronic kidney disease (CKD) patients with parathyroid dysfunction is controversial. Objectives: To investigate the frequency and nature of the tendon involvement in CKD patients undergoing regular hemodialysis, its relationship to parathyroid hormone (PTH) level, using ultrasonograhic examination. Methods: Fifty CKD patients on regular hemodialysis for at least 6 months received a 4-hour dialysis session thrice weekly from El-Sahel Teaching Hospital were included. Patients with Systemic inflammatory diseases, previous trauma and bone fractures, or TB were excluded. After informed consent all the patients were subjected to full medical history, musculoskeletal examination of knee and ankle, laboratory evaluation and ultrasonograhic evaluation of quadriceps and Achilles tendons. Results: The studied group of patients was 27 female and 23 male there mean age was 51.58±12.5 years with dialysis duration from 4.05±2.11 years. Local examination of knees and ankles joints showed that the most frequent sign was ankle joint tenderness in 10 (20%) patients. Ultrasound examination of the Achilles tendons showed that tenderness during probing was the most frequent finding 23 (46%) patients, followed by calcific deposition 12 (24%) patients then abnormal peritendon tissue 10 (20%) patients and abnormal antroposterior (A-P) middle of 1/3 thickness of Achilles tendon 10 (20%) patients patients and the least finding abnormal A-P of distal 1/3 thickness of Achilles tendon 9 (18%) patients and the least finding. But there were no cases of Quadriceps tendon abnormality. Parathyroid hormone level positively correlated with duration of dialysis (p=0.001), serum phosphorus (p<0.001) and some of ultrasound finding as calcific deposit (p=0.01) and increase the middle (p=0.046) & distal (p=0.03) 1/3 thickness of the Achilles tendon. Conclusions: In CKD patients on regular hemodialysis ankle affection was more common than knee affection. In ankle examination, ankle tenderness was the most frequent musculoskeletal sign and the most common ultrasonographic finding was Achilles tendon tenderness during probing then calcific deposits then abnormal peritendon tissue. PTH level was positively correlated with duration of dialysis and presence of calcific deposit and increased antroposterior thickness of Achilles tendon. References: Chen CM, Chu P, Huang GS, Wang SJ, Wu SS. Spontaneous rupture of the patellar and contralateral quadriceps tendons associated with secondary hyperparathyroidism in a patient receiving long-term dialysis. J Formos Med Assoc 2006; 105: 941-5. Brountzos E, Syrgiannis K, Panagiotou I, et al. Ultrasonographic alterations in Achilles tendon in relation to parathormone in chronic hemodialysis patients. J Nephrol. 2009; 22:476-83. Acknowledgements: Acknowledgement to all patients shraing with us in this study. Disclosure of Interest: None declared